Are Consumers Put off by Retargeted Ads on Social Media? Evidence for Perceptions of Marketing Surveillance and Decreased Ad Effectiveness. Issue 2 (1st May 2020) - Farman, Lisa; Comello, Maria Leonora (Nori); Edwards, Jeffrey R.
ABSTRACT: Consumers have described retargeted ads as "creepy, " possibly because these ads cue consumers that marketers are collecting personal data. Participants (N = 280) were either exposed to an ad that was targeted to past online behaviors or a general product ad. Behavioral targeting had a positive direct effect on purchase intent, but it also set off a negative indirect effect. Those exposed to behavioral targeting experienced increased perceived marketing surveillance, which led to increased threat, increased psychological reactance, negative attitudes toward the ad, and negative purchase intention. The indirect cost of perceived marketing surveillance on purchase intent was 4.5 percent.